Cryptorchidism: The dog as a study model - Hernández-Jardón, Norma; Rojas-Castañeda, Julio César; Landero-Huerta, Daniel; Reyes-Cruz, Estefanía; Reynoso-Robles, Rafael; Juárez-Mosqueda, María del Lourdes; Medrano, Alfredo; Reyes-Delgado, Fausto; Vigueras-Villaseñor, Rosa María (Frontiers in Veterinary Science, 2022)
Cryptorchidism (CO) or undescended testicle is an abnormality of male gonadal development that can generate long-term repercussions in men, such as infertility and germ cell neoplasia in situ (GCNIS). The origin of these alterations in humans is not completely clear, due to the absence of an animal model with similar testicular development as in humans with CO. This work intends to describe the testicular histological development of dogs with congenital CO, and determine whether the species could adequately serve as a study model for this pathology in humans. The study was carried out with 36 dogs, equally distributed in two groups: healthy control (CTRL) and CO groups. The contralateral testis to the undescended one in CO group of the animals was considered and analyzed. Each group was subdivided in three stages of development: 1) peripubertal stage (6-8 months), 2) young adult (9-48 months) and 3) senile (49-130 months). Histological development, the presence of cells with gonocyte morphology, cell proliferation, testicular lipoperoxidation and hormonal concentrations of testosterone, estradiol, FSH and LH were evaluated and described. In the cryptorchid testes, the first histological alterations appeared from the first stage of development and were maintained until the senile stage. A pronounced testicular lipoperoxidation occurred only in the second stage of development. The histological alterations due to CO were markedly evident in the young adult stage. Testosterone concentrations witnessed a decrease starting from in the second stage and kept on until the last stage. The contralateral testes of the CO animals showed alterations that positioned them between the control and CO testes. Testicular development of dogs with CO is similar to that of humans. The results of the study suggest that this species could serve as a suitable model for the study of CO in humans.